Nuclear and territorial topography of chromosome telomeres in human lymphocytes - Amrichová, Jana; Lukásová, Emilie; Kozubek, Stanislav; Kozubek, Michal (Experimental cell research, 2003)
Nuclear and territorial positioning of p- and q-telomeres and centromeres of chromosomes 3, 8, 9, 13, and 19 were studied by repeated fluorescence in situ hybridization, high-resolution cytometry, and three-dimensional image analysis in human blood lymphocytes before and after stimulation. Telomeres were found on the opposite side of the territories as compared with the centromeres for all chromosome territories investigated. Mutual distances between telomeres of submetacentric chromosomes were very short, usually shorter than centromere-to-telomere distances, which means that the chromosome territory is nonrandomly folded. Telomeres are, on average, much nearer to the center of the cell nucleus than centromeres; q-telomeres were found, on average, more centrally localized as compared with p-telomeres. Consequently, we directly showed that chromosome territories in the cell nucleus are (1) polar and (2) partially oriented in cell nuclei. The distributions of genetic elements relative to chromosome territories (territorial distributions) can be either narrower or broader than their nuclear distributions, which reflects the degree of adhesion of an element to the territory or to the nucleus. We found no tethering of heterologous telomeres of chromosomes 8, 9, and 19. In contrast, both pairs of homologous telomeres of chromosome 19 (but not in other chromosomes) are tethered (associated) very frequently.
Keywords: lidské chromozomy, pár 19; chromozomy; Cell Nucleus; centromera; Cell Compartmentation; polarita buněk; Chromosomes, Human, Pair 19; Centromere; lidské chromozomy, pár 8; Chromosomes, Human, Pair 8; kompartmentace buňky; buněčné jádro; lymfocyty; lidské chromozomy, pár 13; Interphase; interfáze; lidé; Cell Polarity; Chromosomes; lidské chromozomy, pár 9; Chromosomes, Human, Pair 3; telomery; Humans; lidské chromozomy, pár 3; Lymphocytes; Chromosomes, Human, Pair 9; Chromosomes, Human, Pair 13; Telomere